Growing Pains and Other Things: The Supreme Court of Canada and the Supreme Court of the United States - Hudon, Edward (Revue générale de droit)

(untitled) (Éditions de l’Université d’Ottawa, 1986)
This article is in part a book review and in part a study of two institutions. In it, the author compares the origin and growth of the Supreme Court of Canada and of the Supreme Court of the United States. He uses Professors James G. Snell and Frederick Vaughan's The Supreme Court of Canada: History of the Institution as a starting point, and he compares various aspects of the two Supreme Courts. He points out similarities in the problems that the two have confronted since the beginning, and he indicates the manner in which these problems have been resolved by each.